Effect of varying ethanol and water compositions on the acetone sensing properties of WO3 for application in diabetes mellitus monitoring - Valentine Saasa; Yolandy Lemmer; Thomas Malwela; Amos Akande; Mervyn Beukes; Bonex Mwakikunga (Materials Research Express, 2020)
Tungsten oxide based gas sensors have attracted a lot of attention in breath acetone analysis due to their potential in clinical diagnosis of diabetes. The major problem with this material in sensor application has been remarkable response to all gases but low selectivity to specific gases. Herein, we report the gas sensing performance of WO _3 materials which were synthesized by varying water and ethanol ratios using a facile solvothermal method for acetone detection. The gas sensing properties of as-prepared WO _3 were tested on acetone C _7 H _8 , NO _2 , NH _3 , H _2 S and CH _4 under relative humidity. X-ray diffraction patterns show that as-prepared WO _3 samples are mainly composed of monoclinic WO _3 , a phase having relatively high selectivity to acetone. The as-prepared WO _3 sensors produced using 51:49 ratio of water: ethanol show an increase in acetone response as the acetone concentration increases and a decrease in acetone response as the relative humidity increases. The sensor responded to a very low acetone concentration ranging from 0.5 to 4.5 ppm which is normally found in human breath. Furthermore, the sensor exhibited high sensitivity and selectivity to low ppm of acetone at 100 °C. On contrary, the sensor showed significantly lower response to other gases tested.